KAUSALITAS INFLASI DAN PERTUMBUHAN EKONOMI INDONESIA PERIODE 1965-2013 - Huruta, Andrian Dolfriandra (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2017)
AbstractMacroeconomic deals with the economy as a whole.It examines the behavior of economic aggregates such as gross domestic product, gross domestic product per capita, consumption, investment, inflation, exchange rate, money supply, export, import, unemployment, debt, interest rates, and so forth. Aggregate behavior refers to the behavior of households, companies and countries. This study aims to analyze causality of inflation and economic growth in Indonesia. Study of inflation and economic growth has been done by researchers such as Hartini and Utomo (2004), Setyawati (2006), Maqrobi and Pujiati (2011), Mamo (2012) and Acyuninda (2012), Miskhin (2001), Bofinger (2001), Hervino (2011), Fujiwara (2013), Tutino and Zarazaga (2014), Jahan and Papageorgiou (2014), Trisdian et al. (2014), Christiano and Fitzgerald (2000), Daniel (2007) and Darise (2009) which is see inflation as a monetary phenomenon and fiscal. This study uses secondary data especially the data ofÂ Indonesia current macroeconomic such as economic growth and inflation which published by the World Bank. These data are time series data (time series) from 1965 - 2013. Methodically, this study using Granger causality test to determine the causality of inflation and economic growth. The results shows that there is no causality between inflation and economic growth.Â Keywords: Economic Growth, Inflation, Granger Causality